Serum Vitamin D Level Related to Coffee Consumption in Korean Young Adults Using the 5th Korea National Health and Nutrition Examination Survey - Lim, Hee-Sook (J Bone Metab, 2017)
BACKGROUND: Even young adults are highly interested in their osteological health, yet their calcium intake does not match the level of such interest. Increase in bone loss is known to be associated with higher intake of caffeine and coffee consumption among the young Korean is rising steadily. This study was conducted to reveal the relationship between coffee consumption and serum vitamin D level in Korean young adults. METHODS: This study analyzed potential difference in lifestyle and concentration of vitamin D in blood in relation to coffee intake frequency of 2,523 subjects on the basis of data from the 5th Korea National Health and Nutrition Examination Survey. RESULTS: According to the analysis, groups of males, with high income, frequent social activity followed by alcohol consumption and smoking, and high rate of dining out showed a high frequency of coffee consumption. Vitamin D concentration among the groups was 16.2±5.3 mL and 80.3% of them were considered to be vitamin D-deficient. All the groups appeared to have deficiencies compared to males who did not consume caffeine at all. CONCLUSIONS: The practice of having an adequate amount of coffee is needed, and more efforts should be done to improve vitamin D intake among young adults.